When elites forget their duties: The double-edged sword of prestigious directors on boards - OEHMICHEN, Jana (Institutional Knowledge at Singapore Management University, 2017)
Previous research indicates that the performance effect of prestigious directors is ambiguous. Our study addresses this issue by integrating the theoretical lens of board capital and the institutional perspective. We argue that prestigious directors can bring benefits as well as costs. We claim that the emergence of these costs depends on the institutional context, specifically the institutional characteristics of the country's corporate elite circle which is characterized by the elite cohesion and the elite exclusiveness. Our empirical results with a 15-country sample covering the period of 2005 to 2014 provide evidence for the overall existence of a positive performance effect of prestigious boards. However, our results also indicate that these beneficial effects of prestigious boards are mitigated in countries with high elite exclusiveness. Hence, under these certain institutional conditions, the elite-favouring behaviour of prestigious directors also brings costs.